Inhibition of multiple forms of carbonic anhydrases of spinach chloroplasts by Cu ions - Polishchuk, A.V.; Semenikhin, A.V.; Topchyi, N.M.; Zolotareva, E.K. (Reports of the National Academy of Sciences of Ukraine, 2018)
The influence of Cu2+ on the carbonic anhydrase (CA) activity of various chloroplast fractions is studied. The stromal and thylakoid fractions are obtained after the osmotic destruction of intact chloroplasts washed out from cytosol components. Stromal CAs have been shown to be more sensitive to Cu2+ than the thylakoid CA. So, the halfmaximal inhibition (I50) of the CA activity of the stromal fraction is achieved at a concentration of 3 μM of Cu2+, whereas I50 at the inhibition of thylakoid CA was 10-20 μM Cu2+. In the presence of CuSO4, the distribution of the CA activity on the protein zones of the stromal and thylakoid fractions after the electrophoretic separation is changed: color intensity and the number of colored zones decrease depending on the Cu2+ concentration. The obtained data confirm the possibility of using CA of chloroplasts as a biomarker of the environmental pollution.